PENDEKATAN PEMBELAJARAN SAINS UNTUK MENUMBUHKAN SIKAP ILMIAH DAN KARAKTER SOSIAL PESERTA DIDIK - Syarifuddin, Irdawati; Desma Juita, Ghea Aina Khairunisa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine effective science learning approaches in fostering scientific attitudes and social character in elementary school students. The method used is literature review (library research) by analyzing various sources related to science education, development of scientific attitudes, and social character. Based on the analysis, it was found that Problem-Based Learning (PBL) and Project-Based Learning (PjBL) approaches are effective in developing critical thinking, analytical skills, and student collaboration. These approaches provide students with the opportunity to engage directly in experiments and group discussions that are relevant to everyday life. Additionally, the integration of scientific attitude and social character development in science education is essential to shape students who possess not only high cognitive abilities but also good social skills, such as communication, teamwork, and a sense of responsibility. The implications of this research highlight the importance of teachers' roles in designing and managing lessons that focus not only on academic competencies but also on the development of social character and scientific attitudes. Learning that integrates scientific experiments and social collaboration is expected to create students who are prepared to face the challenges of the 21st century. A balanced approach between individual and collaborative activities needs to be carefully managed to optimally support the development of scientific attitudes and social character